2014
DOI: 10.3748/wjg.v20.i19.5610
|View full text |Cite
|
Sign up to set email alerts
|

Factors that mediate colonization of the human stomach byHelicobacter pylori

Abstract: Helicobacter pylori (H. pylori) colonizes the stomach of humans and causes chronic infection. The majority of bacteria live in the mucus layer overlying the gastric epithelial cells and only a small proportion of bacteria are found interacting with the epithelial cells. The bacteria living in the gastric mucus may act as a reservoir of infection for the underlying cells which is essential for the development of disease. Colonization of gastric mucus is likely to be key to the establishment of chronic infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 147 publications
1
78
0
Order By: Relevance
“…H. pylori cause chronic gastritis and when left untreated can eventually lead to the development of gastroduodenal ulcers and gastric cancer in a subset of infected individuals (5). Although the majority of Helicobacter bacteria remain in the mucus layer lining the gastric epithelium (6)(7)(8), it is widely accepted that the bacteria in contact with epithelial cells cause disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori cause chronic gastritis and when left untreated can eventually lead to the development of gastroduodenal ulcers and gastric cancer in a subset of infected individuals (5). Although the majority of Helicobacter bacteria remain in the mucus layer lining the gastric epithelium (6)(7)(8), it is widely accepted that the bacteria in contact with epithelial cells cause disease.…”
mentioning
confidence: 99%
“…Helicobacter pylori is a Gram-negative, helix-shaped, microaerophilic, human-specific bacterium that colonizes the stomach of more than half of the world's population (5). H. pylori cause chronic gastritis and when left untreated can eventually lead to the development of gastroduodenal ulcers and gastric cancer in a subset of infected individuals (5).…”
mentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) is a spiral-shaped, microaerophilic, gram-negative bacterium that establishes persistent infection in the stomach and causes gastric inflammation, which contributes to the progression of various gastric diseases such as chronic gastritis, gastric ulcers, and gastric cancer (4,24,26,27). Many investigators have reported the relevance of cytokine production to H. pylori infection (23,34).…”
mentioning
confidence: 99%
“…pylori colonizes in the stomach of more than 50% the world's population. Majority of these bacteria occur in the mucus layer of the stomach and may act as a reservoir of infection for the underlying gastric epithelium (Dunne et al, 2014). Moreover, it is widely accepted that the bacteria in contact with epithelial cells initiate disease (Klerk et al, 2016).…”
Section: Resultsmentioning
confidence: 99%